تقييم ممارسات الكادر التمريضي لإجراءات ضبط العدوى في غرفة الولادة في مشفى تشرين الجامعي - عيسى مروان (Latakia University Journal -Medical Sciences Series, 2018)
Infection control is a set of standard procedures performed by health staff during the delivery of health care to the patient, and that achieve the protection of the patient and medical staff from the risk of infection in the hospital departments . there are many factors that predispose to the occurrence of infection during and after labor and delivery. such as birth in non-sterile conditions, and obstructed labor, frequent vaginal examination during labor, retention of parts of the placenta, bleeding, episiotomy, and premature rupture of membrane. The nurse or midwife playing a key role in controlling the infection process during labor and childbirth and after birth by their application of the infection control procedures in delivery room. This study was conducted on a sample of 30 nurses from the Department of Obstetrics at Tishreen University Hospital. The aim of this study were to assessment the compliance of the nursing staff with infection control procedures in the delivery room. The results showed that the majority of the sample Washing the hands, wearing sterile clothing, cleaning the environment, safely disposing of the tools used, ….). This is due to the availability of the necessary equipment and ., the staff experience and application of standards in controlling the infection. The study suggested design and implementation An educational program about the importance and benefits of applying infection control standards in the delivery room to reducing the incidence of infection and thus reducing mortality and morbidity.. ضبط العدوى هي مجموعة الإجراءات المعيارية التي يقوم بها الكادر الصحي أثناء تقديم العناية الصحية بالمريض و التي تحقق حماية للمريض و الكادر الصحي من خطر حدوث الانتان في أقسام المشفى . .يوجد العديد من العوامل التي تؤهب لحدوث الانتان أثناء وبعد المخاض والولادة .مثل الولادة في ظروف غير عقيمة , عسرة المخاض , الفحص المهبلي المتكرر أثناء المخاض ,احتباس اجزاء من المشيمة ,النزف , خزع الفرج الواقي و انبثاق جيب المياه الباكر و تلعب الممرضة او القابلة دورا رئيسا في عملية ضبط العدوى أثناء المخاض و الولادة و بعد الولادة من خلال تطبيقها لاجراءات ضبط العدوى في غرفة الولادة. اجري هذا البحث على عينة قوامها 30 ممرضة من قسم التوليد في مشفى تشرين الجامعي و كان الهذف من هذه الدراسة تقييم مدى تقيد الكادر التمريضي بإجراءات ضبط العدوى في غرفة الولادة .وقد أظهرت النتائج أن غالبية أفراد العينة قد التزمن ب(غسيل اليدين , ارتداء اللباس العقيم و نظافة البيئة و التخلص الآمن من الأدوات المستخدمة و تحضير و ..... ) و هذا عائد الى توافر المستلزمات و المعدات اللازمة لذلك و خبرة الكادر و اتباع الاجراءات المعيارية في ضبط العدوى لذلك اقترحت الدراسة تصميم و تنفيذ برامج تثقيفية حول أهمية و فوائد تطبيق معايير ضبط العدوى في غرفة الولادة في انقاص معدل حدوث الانتان و بالتالي التقليل من معدل الوفيات والامراضيات .